Associations of dog and cat ownership with wheezing and asthma in children: Pilot study of the Japan Environment and children's study - Taniguchi, Yu (PLoS One, 2020)
OBJECTIVES: No previous study has used repeated measures data to examine the associations of dog/cat ownership with wheezing and asthma prevalence among children. This prospective study used repeated measurers analysis to determine whether dog/cat ownership in childhood is an independent risk factor for wheezing and asthma, after adjustment for gestational, socio-economical, and demographical confounders confounders, in Japan. METHODS: We conducted a multicenter pilot study of the Japan Environment and Children's Study (JECS) during 2009–2010. Among 440 newborn infants enrolled, 410 (52.8% males) were evaluated for dog/cat ownership in the home and history of wheezing and asthma in five follow-up questionnaire surveys (until age 6 years). Dog/cat ownership during follow-up period was categorized into four groups: 7.6% were long-term dog/cat owners, 5.9% were toddler-age owners, 5.9% were preschool-age owners, and 80.7% were never owners. RESULTS: The prevalence of wheezing during follow-up period increased from 20.8% to 35.4% and the prevalence of asthma increased from 1.3% to 16.3%. A fitted logistic generalized estimating equation models including important confounders showed no significant associations of the interaction between dog and/or cat ownership and follow-up time with the risks of wheezing and asthma. However, the risks of wheezing and asthma were slightly lower for long-term and toddler-age dog/cat owners than for preschool-age and never owners. CONCLUSIONS: The present findings suggest that dog and cat ownership from toddler-age does not increase the risks of wheezing and asthma compared with never owners among Japanese children.